An investigation of learners' performance in algebra from grades 9 to 11. - Moodley, Vasantha (My University, 2014)
This study is an investigation into the performance of learners in algebra using the levels of understanding as measured by the ICCAMS diagnostic instrument. The study was conducted in two phases. The first phase of the study consisted of an analysis of the scripts of a sample of 29 learners in Grade 9 who had written the test administered by the Wits Maths Connect-Secondary unit at Wits University. The scripts of the same 29 learners in Grade 10 were analysed to determine the progression within the levels of these learners from Grades 9 to 10. Eighteen learners progressed from a lower to a higher level. During the analysis of the tests it was found that the conjoining error was the main obstacle to some learners in progressing from moving from level 1 to level 3. During phase 2 of the study, a sample of 6 learners was selected from the original 29 learners. These learners completed a written task to investigate errors made in algebra in Grade 11. Interviews were conducted with these learners based on a written task. The analysis of the interviews and written task illustrated the problems learners experienced with level 2 questions, particularly with respect to the conjoining error.
Keywords: Algebra--Study and teaching (Secondary)--South Africa.; Academic achievement--South Africa.